Rekonstruksi Pemikiran Pendidikan Agama Islam Ibnu Sina: Implikasinya Terhadap Pembelajaran PAI Kontemporer - Dewi Kirana (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
Ibn Sina's educational thought offers an integrative paradigm between religious knowledge and rational knowledge as a solution to the dichotomy of knowledge that still occurs in contemporary Islamic education. This article examines Ibn Sina's educational concept and its implications for contemporary Islamic Religious Education (PAI) learning. Using the library study method, this research examines Ibn Sina's philosophical thoughts on the objectives of education, curriculum, the role of educators, teaching methods, and the stages of child development. Ibn Sina emphasized the importance of education tailored to the potential, interests, and gradual development of students, as well as the balanced formation of intellect, character, and skills. The curriculum structured based on an integrative and revelation-based approach becomes an important foundation in realizing holistic Islamic education. In the context of contemporary PAI learning, Ibn Sina's thoughts are relevant for building contextual, humanistic, and applicative learning, not only emphasizing cognitive aspects but also affective and psychomotor ones. The reconstruction of Ibn Sina's thought becomes a significant conceptual offer in the development of Islamic education that is adaptive to the challenges of the times.